Observation of a giant mass enhancement in the ultrafast electron dynamics of a topological semimetal - Oliver J. Clark (Nature Portfolio, 2021)
Understanding the coupling between spin-polarised topological surface states and the bulk provides insight into ultrafast spin dynamics. Here, this coupling is shown to be accompanied by a large mass enhancement in the Sb(111) surface electronic structure, leading to unusual dynamics.